Knee joint subchondral bone structure alterations in active athletes: a cross-sectional case–control study. Issue 12 (December 2015) - Roemer, F.W.; Jarraya, M.; Niu, J.; Duryea, J.; Lynch, J.A.; Guermazi, A.
Summary: Objective: It has been shown that trabecular bone structure parameters extracted from radiographs known as fractal signature analysis (FSA) are able to predict structural outcomes such as radiographic osteoarthritis (OA) progression. Little is known about their involvement in early disease or about differences between subjects exposed to increased joint loading such as young active athletes compared to non-athletes. Aim was to compare horizontal and vertical dimensions of bone texture considering athlete status, gender, previous anterior cruciate ligament (ACL) surgery and age. Design: Included were 685 patients of which 135 consecutive athletes (82% soccer players) 18–36 years old and 550 non-athletes controls in the same age range had knee radiography for assessment of subacute or chronic knee complaints. Regions of interest (ROI) were placed in the subchondral medial and lateral tibial plateaus. Fractal signatures were calculated in the horizontal and vertical dimensions. Curve fitting algorithms were applied taking into account all four risk factors in the same model adjusting for each other. Results: For the horizontal dimensions significant differences were observed for gender (estimate (E) 0.098 (95% confidence interval(CI)) (−0.009, 0.008), P < .0001), previous ACL surgery (E −0.031, 95% CI (−0.043, −0.019), P < .0001) and highest age group (E −0.039, 95% CI (−0.048, −0.029), P < .0001). For vertical dimensions, significant differences were shown for athletes (E −0.012, 95% CI (−0.020, −0.004), P < .0001), gender (E 0.056, 95% CI (0.049, 0.062), P < .0001), and age range from 28 to 32 years (E −0.028, 95% CI (−0.037, −0.019), P < .0001). Conclusions: Trabecular bone structure differs between athletes and non-athletes, in regard to previous ACL surgery, gender and higher age.